VIRTUAL FIRE-PROTECTION COMMUNITY - Lovrekovic, Zoran (Journal of process management and new technologies, 2020)
In the first part of the paper, the authors presented the problems which our subjects from the fire-protection area in their beginnings, development and work encounter. As a solution which the authors suggest is the use of the Internet, as a medium that provides a simple, easy and cheap overcoming the geographical and time barriers in the flow of the (necessary) information. While building the site that should offer assistance to the FP subjects, it is necessary to define the goals and to build a strategy to achieve the goals through internet site. In this paper the authors suggested several possible approaches: Web site with statistic contents, Web site with dynamic contents, Web site with dynamic contents and two-way flow of information and Web site for knowledge management. VFPC (virtual fire-protection community) would be a legal counsel, a dot-com company, and basically a community of all stake-holders considering FP. So, VFPC does not have its own premises or assets. It is situated in a "virtual reality", i.e. it is a Web portal which exists owing to joint activity of several subjects.
Keywords: Web site; fire-protection; virtual community; virtual fire-protection